2022
DOI: 10.1186/s12889-022-13679-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with self-reported HIV testing among adolescent girls and young women in Rwanda: evidence from 2019/20 Rwanda Demographic and Health Survey

Abstract: Background HIV/AIDS remains a major public health problem globally. The majority of people living with HIV are from Sub-Saharan Africa, particularly adolescent girls and young women (AGYW) aged 15-24 years. HIV testing is crucial as it is the gateway to HIV prevention, treatment, and care; therefore this study determined the prevalence and factors associated with self-reported HIV testing among AGYW in Rwanda. Methods We conducted secondary data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 19 publications
8
23
0
Order By: Relevance
“…Moreover, region was also found to be associated with risk factors for HIV, where the western region compared to Kigali had lower odds of facing HIV risk factors. The western province is a rural area with less activity and entertainment places like bars where women are less likely to participate in risky sexual behaviours [19]. The study nds are consistent with studies in Eswatini [42] which reported that women in rural areas are likely to have a limited number of lifetime sexual partners hence reducing the risk for HIV.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Moreover, region was also found to be associated with risk factors for HIV, where the western region compared to Kigali had lower odds of facing HIV risk factors. The western province is a rural area with less activity and entertainment places like bars where women are less likely to participate in risky sexual behaviours [19]. The study nds are consistent with studies in Eswatini [42] which reported that women in rural areas are likely to have a limited number of lifetime sexual partners hence reducing the risk for HIV.…”
Section: Discussionsupporting
confidence: 87%
“…The ndings are similar to other studies in Swaziland [32], Sierra Leone [1], Zambia [20] and China [33]. This may be because older women 25-34 and 34-44 years were probably more informed about sexual matters and more knowledgeable about HIV [19] whereas younger women are generally explorative and easily fall victim to peer pressure hence easily indulging in risky sexual behaviours [1,33].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In Rwanda, some studies have been conducted around HIV and its prevalence amongst others [ 5 , 13 ] [ 21 24 ]. The focus of these studies has largely been identifying HIV incidence and prevalence at the district level [ 5 ], risk factors and characteristics of mothers living with HIV [ 13 ] and rates of MTCT of HIV at 6–10 weeks postpartum [ 21 ] amongst others.…”
Section: Introductionmentioning
confidence: 99%